PENGARUH EFEKTIVITAS DAN KUALITAS PELAYANAN BALIK NAMA TERHADAP KEPUASAN MASYARAKAT DI KANTOR PERTANAHAN KOTA BANDUNG - Sabbila Agustina; Susniwati Susniwati; Rezky Afiahtul Barokah (Universitas Bina Taruna Gorontalo, 2023)
This study aims to find out how the effectiveness and quality of services on community satisfaction at the Bandung City Land Office and what are the factors that influence the effectiveness and quality of services on community satisfaction at the Bandung City Land Office. This research was conducted using a quantitative method with a sample of 30 respondents who visited the Bandung City Land Office. Data analysis in this study used multiple linear regression. Multiple linear regression is used to analyze the effectiveness (X1) and service quality (X2) variables affecting community satisfaction (Y). The results of this study indicate that the effectiveness and service quality of the Bandung City Land Office have a positive effect on community satisfaction. Every employee in providing forms of service prioritizes aspects of service that greatly influence the behavior of people who receive services, so that the ability of employees to serve the community is needed in accordance with the level of absorption, understanding, incompatibility of various forms of service that they do not know.